"There's no Reason why": A Campaign to Raise Cancer Awareness among Adolescents. Issue 3 (May 2016) - Magni, Chiara; Maggioni, Francesca; Ricci, Angelo; Barisone, Elena; Jankovic, Momcilo; Postiglione, Emma Sarlo; Cargnel, Enrica; Barricelli, Barbara Rita; Valtolina, Stefano; Veneroni, Laura; Chiaravalli, Stefano; Lapidari, Pietro; et al.
Introduction: Adolescents with cancer often experience a longer diagnostic delay than children, mainly because they take longer to go to a doctor. The Italian Society for Adolescents with Oncohematological Diseases (SIAMO) has launched an information campaign focusing on raising adolescents' awareness of the importance of diagnosing cancer early. Methods: The concepts of the campaign were developed by a scientific committee of clinicians, cancer patients and their parents, and marketing experts. The title of the campaign is "There's no reason why". A video has been launched on TV channels and the Internet, and the final frame refers viewers to the SIAMO website, which provides advice to help adolescents interpret any symptoms they experience. Results: The video has had 12, 181 views. In the 6 months following the launch of the campaign, the SIAMO website page dedicated to the campaign was opened by 9, 767 viewers for a total of 13, 632 views. Conclusions: Though it remains very difficult to judge the efficacy of this initiative, the value of a campaign focusing on improving the adolescent population's cancer awareness is supported by the large number of studies published on the diagnostic delay in this age group. Our campaign goes to show the importance of ensuring cooperation between the different stakeholders involved in the global care of adolescents with cancer.